Re-thinking Democracy in Resistance: A Theoretical Approach to Social movements, Collective Action, Social Transformation and Political Subjects - Gallo-Gómez, Juan Camilo; Justus Liebig University Giessen (My University, 2023)
This work intends to focus on social movements as the core of political action under the current political conditions. Democracy is understood as the action of transformation toward emancipation and inclusion, not just as a set of institutions or legal standards. I try to go beyond the defense of a specific institutional design or propose new institutional designs. My goal is to highlight the role of communicative dissent and the appearance in the public sphere of the real experiences of injustice to construct a participatory model of democracy that complements and serves as a critique of traditional republican and liberal visions of consensus and rational deliberation. I also try to give to the idea of political participation the concrete historical content from the experience of injustice as the source of social transformation. I suggest that democracy should be understood as a constant process of resistance and conflict for the normative field of justification of social order and the exercise of political power.
Keywords: Democracy; Social Movements; Resistance; Collective Action; Social Transformation; ddc:100; ddc:320